Analysis of the Implementation of Participatory Principles to Improve Democracy: A Case Study in Sukopuro Village Government, Jabung District, Malang Regency - Mukhammad Soleh; Sinda Eria Ayuni; Marsudi Dedi Putra; Dian Utami Ikhwaningrum; Bayu Firmanto; Galih Setyo Refangga; Sigid Budi Santoso; Intan Rachmawati; Imaniar Juang Hayati; Sulistya Diah Paramitha; Aghniya Ariza Sa’adah (Jurnal Multidisiplin Madani, 2023)
Community participation is one of the principles of implementing good village governance. This study aims to analyze the implementation of participatory principles in village government. This research uses empirical legal research methods, primary data collection through interviews and observations as well as literature studies, and uses sociological juridical analysis through data distribution, data reduction and conclusion making. The results showed that the village government has applied the participatory principle. This can be seen from the pattern of drafting Village Regulations and determining the Village Revenue and Expenditure Budget (APB Desa), where the community is included in village development planning, through hamlet-level deliberations and the results of hamlet-level deliberations are brought to village-level deliberations called Village Development Planning Deliberation (Musrenbangdes). Community involvement in Musrenbang is one form of implementing village democracy